Kompleksometri Kalsium dan SSA Timbal Beberapa Depot Air Isi Ulang di Medan - Nur’Adina; Hendri Faisal; Suprianto (Jurnal Indah Sains dan Klinis, 2021)
Calcium minerals play an important role in maintaining body functions, while Lead is a dangerous heavy metal. The research was aimed at determining the levels of Calcium and Lead from several refill water depots in Medan. Calcium complexometry and lead AAS as their respective assay methods. Research shows calcium levels are 10.3-29.3 mg/L, correlation coefficient is 0.9928, and no lead is found in refill drinking water. Calcium levels do not meet the requirements, while lead levels still meet the WHO requirements.